2016
DOI: 10.1007/s00167-016-3991-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pubescent posterior cruciate ligament (PCL) reconstruction using maternal allograft

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Only two studies [13, 24] investigated the outcomes of PCL reconstruction for a series of pediatric patients. Shah et al [24] reported a series of three patients, and Kocher et al [13] reported the results of eight patients with a mean age of 16.5 years. The mean Pedi‐IKDC and Lysholm scores in those studies were 81.3 and 80.1, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies [13, 24] investigated the outcomes of PCL reconstruction for a series of pediatric patients. Shah et al [24] reported a series of three patients, and Kocher et al [13] reported the results of eight patients with a mean age of 16.5 years. The mean Pedi‐IKDC and Lysholm scores in those studies were 81.3 and 80.1, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on this topic is sparse and dominated by case reports. Only two studies [13, 24] investigated the outcomes of PCL reconstruction for a series of pediatric patients. Shah et al [24] reported a series of three patients, and Kocher et al [13] reported the results of eight patients with a mean age of 16.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…This was not demonstrated in the included study using this as the primary technique 28 or in the previous documented case series. 23 There were several limitations to our study. First, this systematic review included entirely level 4 evidence with no prospective studies and small sample sizes.…”
Section: Discussionmentioning
confidence: 93%
“…30 The findings pertaining to angular deformity and LLDs have been supported by previous case reports and other reports included in this review. 1,10,11,23,28 The physis-sparing technique aims to avoid physeal injury by drilling tunnels away from the physis. However, reconstructing the PCL in skeletally immature patients requires placing the tibial tunnel distal to the physis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation